2019
DOI: 10.1108/mrr-06-2018-0235
|View full text |Cite
|
Sign up to set email alerts
|

Ethical leadership and productive work attitudes among micro financial institutions in Ghana

Abstract: Purpose Ethical leadership wields a significant influence on productive work attitudes of employees. The relationship may partly be because of existing conditions in the organization. However, there is dearth of research on the impact that conditions in the organization affect work attitudes and other employee behaviours. Thus, the purpose of this study is to examine organizational climate as an explanatory mechanism for the relationship between ethical leadership and employees’ productive work attitudes (empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…Punwatkar and Verghese (2018) found out that when the respondents perceived favorable organizational climate, the relationship of competencies and job performance is stronger and significant. Likewise, Addai et al (2019) were able to establish through hierarchical regression analyses that the relationship of employees working in micro financial institutions tends to show high productive work attitudes under ethical leadership when there is high level of organizational climate. However, when it comes to the topic on career development, it was observed that no study has been conducted yet on the significant relationship and how it moderates the career development constructs such as career adaptability and career intention.…”
Section: Organizational Climatementioning
confidence: 99%
“…Punwatkar and Verghese (2018) found out that when the respondents perceived favorable organizational climate, the relationship of competencies and job performance is stronger and significant. Likewise, Addai et al (2019) were able to establish through hierarchical regression analyses that the relationship of employees working in micro financial institutions tends to show high productive work attitudes under ethical leadership when there is high level of organizational climate. However, when it comes to the topic on career development, it was observed that no study has been conducted yet on the significant relationship and how it moderates the career development constructs such as career adaptability and career intention.…”
Section: Organizational Climatementioning
confidence: 99%
“…Ethical leadership is an essential component of work productivity because it can influence the workplace behaviours of employees. In Ghana, the working class is more than those who are not gainfully engaged (Addai, Avor, Ofori, & Tweneboah, 2019). Addai et al (2019) argue that among those who are engaged, the majority of them are public sector workers.…”
Section: The Ghanaian Contextmentioning
confidence: 99%
“…In Ghana, the working class is more than those who are not gainfully engaged (Addai, Avor, Ofori, & Tweneboah, 2019). Addai et al (2019) argue that among those who are engaged, the majority of them are public sector workers. With these public sector workers dominating the working class, it is rumoured that several deviant work behaviours emanate from ethical leadership in most public institutions (Dampson, 2021).…”
Section: The Ghanaian Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, designing the appropriate strategies to motivate the workforce in this direction appears as one of the critical aspects of the productivity management. Addai et al (2019) indicated that ethical leadership has a significant impact on the productive work attitudes and employee behavior, and the relationship between the ethical leadership and the productive work attitudes is positive. Anderson and Raissi (2022) reinforces the need for distinguished leadership that works to re-grow the productivity of the projects as a result of the lack of successful management, with a focus on the proactive productivity, and production flexibility.…”
Section: Ho1-2mentioning
confidence: 99%